An Innovative and Economical Device for Ischemic Preconditioning of the Forehead Flap Prior to Pedicle Division: A Comparative Study - Xiao, Wentian; Ng, Sally; Li, Hua; Min, Peiru; Feng, Shaoqing; Su, Weijie; Zhang, Yixin (Journal of Reconstructive Microsurgery, 2022)
Background Ischemic preconditioning of the forehead flap prior to pedicle division helps to improve angiogenesis. Clamping the pedicle by a clamped rubber band with vessel forceps is often clinically applied. However, the severe pain and unstable blocking effect influenced the preconditioning process. In this study, we described an innovative device designed for ischemic preconditioning and compared its efficacy with the clamped rubber band.Methods The device consists of a self-locking nylon cable tie with a buckle and a rubber tube. The rubber tube is fed over the cable tie to act as a soft outer lining and the cable tie is tightened across the pedicle to block the perfusion for ischemic preconditioning. This device and the standard clamped rubber band were applied respectively before division surgery. The constriction effect, reliability, reproducibility, and the patients' pain tolerance were compared.Results A total of 20 forehead flaps were included. The cable tie had less incidence of loosening (7.7% vs. 16.6%, p < 0.05) and maintained the pressure more effectively. The pain score for the nylon cable tie was significantly lower than the clamped rubber band (4.25 ± 1.02 vs. 6.75 ± 1.12, p < 0.05), especially for 10 pediatric patients (4.50 ± 0.85 vs. 8.10 ± 1.20, p < 0.01). All 20 pedicles were successfully divided at 19 to 22 days with no surgical complications.Conclusion Compared with the clamped rubber band, the cable tie produces a more reliable and reproducible ischemic preconditioning effect. It is also better tolerated by the patients. Therefore, we recommend using the nylon cable tie as the preferred device for ischemic preconditioning of the forehead flap.
Keywords: forehead flap; ischemic preconditioning; pedicle division; pedicle clamping device; nasal reconstruction